Pengembangan E-Modul Biologi Berbasis Flip Pdf Corporate Bagi Siswa Kelas X SMAN 1 Pamboang Kabupaten Majene - Rifkanita, Dian (Universitas Negeri Makassar, 2023)
This study is a research and development that aims to produce a product of Biology e-module based on a flip pdf corporate for students at SMAN 1 Pamboang in Majene district. This research and development referred to the ADDIE design development model consisted of five stages: analysis, design, development, implementation, and evaluation. The research instruments used were instrument validation sheet, teacher’s response questionnaire, students’ response questionnaire, and learning outcomes test. The sample of this study was the students of grade X at SMAN 1 Pamboang in Majene district. The results of data analysis show that: 1) the Biology e-module based on flip pdf corporate on Ecosystem material meets the criteria for validity with a mean score of 4.6, 2) the Biology e-module based on flip pdf corporate on Ecosystem material meets the practicality criteria based on the result of the teacher's response with an average of 93% in solid category and 7% in strong category, while the students’ response with an average of 50% is in strong category and 36.6% is in solid category, 3) the Biology e-module based on flip pdf corporate on Ecosystem material meets the criteria of effectiveness with the percentage of completeness of learning outcomes 70.8% in effective category. Based on the results of the study, it can be concluded that the Biology e-module based on flip pdf corporate on Ecosystem material has met the valid, practical, and effective criteria. In addition, the results obtained from cross tabulation between students’ responses and learning outcomes with the asymptotic significance of 0.024 < 0.05, so it can be concluded that there is a relationship between practicality and effectiveness of the Biology e-module based on flip pdf corporate.